The negative impact of living environment on intelligence quotient of primary school children in Baghdad City, Iraq: a cross-sectional study - Ghazi Hasanain; Isa Zaleha; Aljunid Syed; Shah Shamsul; Tamil Azmi; Abdalqader Mohammed A (BMC, 2012)
Abstract Background Environmental factors play a very important role in the child development process, especially in a situation like that of Iraq. Thirteen years of economic sanctions followed by the 2003 war and 8 years of unstable security have affected the daily life of Iraqi families and children. The objective of this study was to assess the associations between living environment domains and child intelligence quotient (IQ) score. Methods A cross-sectional survey was conducted among 529 children aged 7-8 years from five primary schools in Baghdad during September-October, 2011. The five schools represent people living a range of conditions, and include of both high and low socio-economic groups. Living environment was assessed by 13 questionnaire items, consists of three domains: physical safety , mental stress and public services. While IQ was assessed by Raven Colored progressive matrices. Results Among the participants, 22% were of low intelligence versus 77% of high intelligence and 19% lived in a poor environment. There were significant associations between the mental stress and service living environment domains and child IQ (p = 0.009 and p = 0.001, respectively). Conclusion In Iraq, child IQ was found to be associated with the mental stress and service domains of the living environment. This study findings will help authorities in their efforts to improve living environment.